VAMOS A APRENDER ESPANOL LENGUA EXTRANJERA - Salina Husain (Penerbit UTHM, 2005)
Recently Malaysia is exposed with a lot of films and songs from Latin America where most of them, Spanish as the lingua franca. This current scenario has increased interest and blazed desire among Malaysians to get to know more about Spanish. This book is designed for understanding in Spanish. This course book covers basic grammar, comprehension, vocabulary and phrases. This book is also equiped with exercise to test the reader’s level of understanding and achievements.